Cuando la prensa incomoda al sistema político: la libertad de imprenta frente a la propuesta de José María Gutiérrez de Estrada de 1840 - Villavicencio Navarro, Víctor (El Colegio de México, A.C., 2019)
This article analyzes how the freedom of the press was understood in Mexico just before the midpoint of the 19th Century, as well as the elements that shaped its exercise. In the autumn of 1840, a pamphlet was published in Mexico City that proposed monarchical government as a solution to the country’s problems. The rejection of the pamphlet’s proposal was unanimous and the author and publisher were put on trial for its subversive content. The outcry that followed led to a discussion on the importance of the press for Mexico and accusations that the government had threatened its freedom by arresting them. Primarily based on the contemporary press and legal decrees, this article analyzes the reactions to the publication of this pamphlet and its consequences, showing the role of the press in the world of politics, the strategies used by the government to regulate it, the way in which the relevant laws were interpreted and applied and the reciprocal relationship between the activities of the press and the political panorama. This article contributes to the interpretation of the press (pamphlets, printers, writers) as an actor, sometimes a leading one, in the politics of 19th Century Mexico and the freedom of the press as a right that had to be closely regulated.